Effect of postural control in individuals with mild cognitive impairment after Pilates training: A clinical trial study - Aynollah Sakinepoor; Amir Letafatkar; Aynollah Naderi; Amir Hossein Hashemian; Zhara Nourozi; Mohmmad Alimoradi (مجله دانشگاه علوم پزشکی گرگان, 2021)
Background and Objective: One of the most common complications of mild cognitive impairment is increased body sway and falls. This study was performed to evaluate the effect of Pilates training on control posture in patients with mild cognitive impairment. Methods: This clinical trial study was performed on 30 women with mild cognitive impairment who referred to elderly Research Center in Kermanshah city, north-west of Iran during 2019. Subjects were randomly divided into two groups including Pilates Training and control groups. Pilates training group was trained for eight weeks, 3 sessions per week and duration for each session was one hour. The control posture of the subjects before and after the exercise was evaluated. Results: There was significant difference in obtained scores in the size and distance of the center of pressure area range with open and closed eyes in the intervention group, prior and after training (P<0.05). The mean postural control (the size and distance of the center of pressure area range with open and closed eyes) reduced after 8 weeks of Pilates exercises in the intervention group in compared to control group (P<0.05). Conclusion: Pilates training is effective in improving postural control in patients with mild cognitive impairment.